Memoria y lenguaje en un adolescente con discapacidad intelectual leve. - Jaramillo Enríquez, Nicole Anahí; Obando Quevedo, Scarlet Dayanara (Machala: Universidad Técnica de Machala, 2024)
The present research analyzes the relationship between language and memory in an adolescent with mild intellectual disability (MID), a condiion characterized by below-average intellectual and adaptive functioning. The central problem posed is: What is the relationship between language and memory in an adolescent with mild intellectual disability? The general objective is to determine and propose inclusive pedagogical strategies that promote the adolescent's overall development, facilitating their school and social integration. Through a qualitative and explanatory approach, tools such as the Wechsler Intelligence Scale for Children (WISC-V) and Neuropsy were used to analyze the cognitive, linguistic, and social capacities of the participant. The results show significant deficiencies in phonological memory, logical reasoning, and oral language, affecting their academic and social performance. Inclusive pedagogical strategies are proposed, such as the use of visual supports, phonological memory exercises, and curricular adaptation, to promote their overall development. This research highlights the importance of designing educational interventions based on individual strengths and needs, contributing to the school and social integration of adolescents with MID. By addressing these problems and objectives, the aim is not only to improve the participant's cognitive and linguistic skills but also to increase their autonomy and quality of life. The research emphasizes that a holistic and personalized approach in the educational field is essential to achieve these goals, significantly contributing to the adolescent's overall well-being and integration into the school community.
La presente investigación analiza la relación entre el lenguaje y la memoria en un adolescente con discapacidad intelectual leve DI leve, condición caracterizada por un funcionamiento intelectual y adaptativo inferior al promedio. Teniendo como problema central. Qué relación tiene el lenguaje con la memoria en un adolescente con discapacidad intelectual leve Y como objetivo determinar y proponer estrategias pedagógicas inclusivas que promuevan el desarrollo integral del adolescente, facilitando su integración escolar y social. A través de un enfoque cualitativo y explicativo, se emplearon herramientas como la Escala de Inteligencia de Wechsler para Niños WISC-V y Neuropsy para analizar las capacidades cognitivas, lingüísticas y sociales del participante. Evidenciando en la investigación deficiencias significativas en la memoria, el razonamiento lógico y el lenguaje oral, afectando su desempeño académico y social. Se proponen estrategias pedagógicas inclusivas, como el uso de apoyos visuales, ejercicios de memoria fonológica y adaptación curricular, para promover su desarrollo integral. Esta investigación destaca la importancia de diseñar intervenciones educativas basadas en las fortalezas y necesidades individuales, contribuyendo a la integración escolar y social de adolescentes con DI leve. Al abordar estos problemas y objetivos, se busca no solo mejorar las habilidades cognitivas y lingüísticas del participante, sino también aumentar su autonomía y calidad de vida. La investigación enfatiza que un enfoque holístico y personalizado en el ámbito educativo es esencial para lograr estos fines, contribuyendo significativamente al bienestar general del adolescente y su integración en la comunidad escolar.
Keywords: DISCAPACIDAD INTELECTUAL; MEMORIA; LENGUAJE; INTERVENCIÓN